Structured on-the-job training to improve retention of newborn resuscitation skills: a national cohort Helping Babies Breathe study in Tanzania - Drake, Mary (BMC Pediatr, 2019)
BACKGROUND: Newborn resuscitation is a life-saving intervention for birth asphyxia, a leading cause of neonatal mortality. Improving provider newborn resuscitation skills is critical for delivering quality care, but the retention of these skills has been a challenge. Tanzania implemented a national newborn resuscitation using the Helping Babies Breathe (HBB) training program to help address this problem. Our objective was to evaluate the effectiveness of two training approaches to newborn resuscitation skills retention implemented across 16 regions of Tanzania. METHODS: An initial training approach implemented included verbal instructions for participating providers to replicate the training back at their service delivery site to others who were not trained. After a noted drop in skills, the program developed structured on-the-job training guidance and included this in the training. The approaches were implemented sequentially in 8 regions each with nurses/ midwives, other clinicians and medical attendants who had not received HBB training before. Newborn resuscitation skills were assessed immediately after training and 4–6 weeks after training using a validated objective structured clinical examination, and retention, measured through degree of skills drop, was compared between the two training approaches. RESULTS: Eight thousand, three hundred and ninety-one providers were trained and assessed: 3592 underwent the initial training approach and 4799 underwent the modified approach. Immediately post-training, average skills scores were similar between initial and modified training groups: 80.5 and 81.3%, respectively (p-value 0.07). Both groups experienced statistically significant drops in newborn resuscitation skills over time. However, the modified training approach was associated with significantly higher skills scores 4–6 weeks post training: 77.6% among the modified training approach versus 70.7% among the initial training approach (p-value < 0.0001). Medical attendant cadre showed the greatest skills retention. CONCLUSIONS: A modified training approach consisting of structured OJT, guidance and tools improved newborn resuscitation skills retention among health care providers. The study results give evidence for including on-site training as part of efforts to improve provider performance and strengthen quality of care. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12887-019-1419-5) contains supplementary material, which is available to authorized users.